SOSIALISASI PEMILIHAN DAN PENGGUNAAN BAHAN LOKAL UNTUK MASAKAN DI 3 NEGARA (INDONESIA, MALAYSIA DAN TAIWAN) - Hastiningsih, Wahyu Tri; Ismail, Farida Hanim; Chang, Ti Yu (Bengawan : Jurnal Pengabdian Masyarakat, 2023)
The implementation of community service carried out internationally with zoom media, involving participants from 3 countries namely Indonesia, Malaysia and Taiwan with partners from hospitality students and the general public aims to introduce various dishes using local ingredients. This community service also focuses on how to choose good ingredients and introduce local ingredients and spices from Indonesia that are used in cooking. The method used in this service is by presenting material and discussion The technique of selecting good Indonesian ingredients and spices is shown directly so that participants, especially from Malaysia and Taiwan, can find out firsthand. With this activity, it becomes a forum to introduce Indonesian cuisine to the international scene.